Global financial instability and implications for the GCC - Rubin, Jonathan 1962- (Emirates lecture series, 2013)
"Many aspects of the global economic crisis remain unclear, especially the ability of the United States (US) and the European Union (EU) to reduce their operating deficits and debt. In particular, one major concern for those focused on climate change is the extent to which the financial crisis has impacted the United States' and EU's ability and willingness to invest in and help develop renewable energy technology around the world. This is a serious concern since there is now a consensus that climate change is human-induced. Equally important, there is a need to reduce the non-climate impacts of energy generation, provide employment, and reduce global poverty."--Summary.